Monocyte subset distribution and surface expression of HLA-DR and CD14 in patients after cardiopulmonary resuscitation - Alexander Asmussen (Nature Portfolio, 2021)
Abstract Systemic inflammation is a major feature of the post-cardiac arrest syndrome. The three monocyte subpopulations are thought to play an important role in this inflammatory state because they are endowed with numerous pattern recognition receptors, such as CD14, that have been associated with ischemia–reperfusion injury. By contrast, an exaggerated antiinflammatory response has also been described following cardiac arrest, which may be mediated by downregulation of antigen presentation receptor HLA-DR. We report the composition of monocyte subpopulations and the expression of CD14 and HLA-DR following cardiac arrest. Blood specimens were collected from 32 patients at three timepoints in the first 48 h after cardiac arrest. Monocyte subset composition was determined by flow cytometry based on the expression of CD14, CD16, and HLA-DR. Monocyte subset composition and the expression of CD14 and HLA-DR were correlated with patient outcomes. The results were compared to 19 patients with coronary artery disease. Cardiac arrest patients showed a significant decline in the percentage of nonclassical monocytes. Monocyte CD14 expression was upregulated after 24 h and correlated with the time to return of spontaneous circulation. Downregulation of HLA-DR expression was observed mainly among classical monocytes and significantly correlated with the dose of norepinephrine used to treat shock. Downregulation of HLA-DR among nonclassical and intermediate monocytes was significantly associated with disease severity. Our data demonstrate the disturbance of monocyte subset composition with a significant decline in nonclassical monocytes at an early stage following cardiac arrest. Our findings suggest the simultaneous presence of hyperinflammation, as evidenced by upregulation of CD14, and monocyte deactivation, characterized by downregulation of HLA-DR. The extent of monocyte deactivation was significantly correlated with disease severity.